2020
DOI: 10.3389/fonc.2020.599907
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Metrics Are Correlated to the Pathological Response in Esophageal Cancer Patients Treated With Induction Chemotherapy Followed by Neoadjuvant Chemo-Radiotherapy

Abstract: Background and ObjectiveThe aim of this study was to assess the ability of Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F-FDG PET/CT) to provide functional information useful in predicting pathological response to an intensive neoadjuvant chemo-radiotherapy (nCRT) protocol for both esophageal squamous cell carcinoma (SCC) and adenocarcinoma (ADC) patients.Material and MethodsEsophageal carcinoma (EC) patients, treated in our Center between 2014 and 2018, were retrospectively reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Studies that performed imaging before and after treatment reported that tumor heterogeneity generally decreased following treatment [ 43 , 52 ]. Simoni et al found that metabolic TV (MTV) in poor responders was significantly higher than in good responders (38.6 mL vs. 17.7 mL, p = 0.02) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies that performed imaging before and after treatment reported that tumor heterogeneity generally decreased following treatment [ 43 , 52 ]. Simoni et al found that metabolic TV (MTV) in poor responders was significantly higher than in good responders (38.6 mL vs. 17.7 mL, p = 0.02) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies on esophageal cancer were included in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]; 1 used 18F-FDG and 18F-FLT, reporting no significant results regarding 18F-FLT [ 10 ]. The remaining 23 studies employed only 18F-FDG.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies testing inter-institutional generalisability demonstrated performance decreases [ 25 , 41 ], indicating that some degree of overfitting occurred. Lack of external validation was frequently cited as a limitation [ 6 , 25 , 27 , 29 31 , 41 ]. Of five studies which performed internal validation, only Foley reported the performance of a single finalised model on test data which was unobserved during training or model selection [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simoni modelled CRT response retrospectively on a prospective 18F-FDG PET data from patients with locally advanced disease at a single institution (TRIPOD: 23, RQS: 3) [ 29 ]. Thirty-five out of 53 patients had adenocarcinoma.…”
Section: Therapeutic Responsementioning
confidence: 99%